Kensuke's kingdom - Morpurgo, Michael; Foreman, Michael (Egmont London, 2017)
After losing his job, Michael's father surprises the family by purchasing a yacht in which they will sail around the world. In the first weeks at sea, Michael, his parents, and his dog, Stella, zigzag from England to Australia and across the Coral Sea, where Michael's reverie comes to a frightening end